2017
DOI: 10.32505/jebis.v2i1.119
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Financial Inclusion Terhadap Pemberdayaan Masyarakat Miskin Di Medan (Studi Kasus Pembiayaan Mikro Ss Ii Di Bank Sumut Syariah)

Abstract: This research aims to analyze the financial inclusion towards the empowerment of the poor in Medan through financing Sumut Sejahtera of the Bank Sumut Syariah. More specifically the research aims to know 1) the concept of financial inclusion that is implemented as a means of expanding access to financial services of banks and non-banks, 2) the application of the financial inclusion  Bank Sumut Syariah. Bank Sumt Syariah have significant role in the economic development of the community through a variety of fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…PNM has an effect on the development of Ultra Micro businesses in an area (Perwitasari, 2017). A previous study conducted by Cupian Deny Febriandani revealed that the form of contract transactions carried out by BPRS PNM Mentari affected the development of Ultra Micro businesses in Garut Regency (Cupian & Febriandani, 2019). Furthermore Fitri Dian Perwitasari revealed that the financing program at PT.…”
Section: Literature Review (If Any) Murabahah Financing At Pt Pnm Mek...mentioning
confidence: 93%
“…PNM has an effect on the development of Ultra Micro businesses in an area (Perwitasari, 2017). A previous study conducted by Cupian Deny Febriandani revealed that the form of contract transactions carried out by BPRS PNM Mentari affected the development of Ultra Micro businesses in Garut Regency (Cupian & Febriandani, 2019). Furthermore Fitri Dian Perwitasari revealed that the financing program at PT.…”
Section: Literature Review (If Any) Murabahah Financing At Pt Pnm Mek...mentioning
confidence: 93%
“…Besides the sharia banking industry, the sharia pawnshop industry and sharia financing institutions have a sharia financial literacy index that is relatively larger than other sharia financial industries. Strategic programs must be implemented to develop Islamic finance, significantly optimising the promotion of Islamic finance to increase public literacy and preferences because of the low Islamic financial literacy in Indonesia (Khan & Arif, 2022;H. Nasution, 2017).…”
Section: Islamic Financial Literacymentioning
confidence: 99%
“…Hal ini juga membuat akses serta kondisi wilayah geografis menjadi suatu target perbankan agar lebih dekat kepada masyarakat, dan tidak menegaskan bahwa layanan jasa keuangan hanya menjadi milik sekelompok masyarakat di perkotaan saja. Dalam arti, adanya masyarakat unbankable di suatu daerah disebabkan karena sulitnya akses lembaga jasa keuangan, monopoli bank pada sektor-sektor tertentu dan terbatasnya saluran distribusi keuangan (Nasution, 2017). Berdasarkan hal ini, diharapkan seluruh lapisan masyarakat dapat menikmati layanan jasa keuangan tanpa terkecuali, dan otomatis ini dapat meningkatkan tingkat inklusi keuangan di suatu daerah bahkan negara.…”
Section: Hasil Dan Pembahasan 1 Perbankan Dan Lembaga Financial Techunclassified